Exercise prevents downregulation of hippocampal presynaptic proteins following olanzapine-elicited metabolic dysregulation in rats: Distinct roles of inhibitory and excitatory terminals. (20th August 2015) - Ramos-Miguel, A.; Honer, W.G.; Boyda, H.N.; Sawada, K.; Beasley, C.L.; Procyshyn, R.M.; Barr, A.M.
Highlights: Chronic olanzapine reduced key neurosecretory proteins in rat hippocampus, including syntaxin-1, SNAP-25 and VAMP. Presynaptic protein loss did not affect the amount of SNARE complex protein–protein interactions. Protein depletion was greater in the GABAergic terminals within the dentate gyrus and in CA3 mossy fibers. Lower presynaptic protein levels were associated with olanzapine-induced glucose intolerance and reduced CA1 volume. Routine exercise partially prevented olanzapine-induced deleterious effects in rat hippocampus. Abstract: Schizophrenia patients treated with olanzapine, or other second-generation antipsychotics, frequently develop metabolic side-effects, such as glucose intolerance and increased adiposity. We previously observed that modeling these adverse effects in rodents also resulted in hippocampal shrinkage. Here, we investigated the impact of olanzapine treatment, and the beneficial influence of routine exercise, on the neurosecretion machinery of the hippocampus. Immunodensities and interactions of three soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins (syntaxin-1, synaptosome-associated protein of 25 kDa (SNAP-25) and vesicle-associated membrane protein (VAMP)), synaptotagmin and complexins-1/2 were quantified in the hippocampus of sedentary and exercising rats exposed over 9 weeks to vehicle ( n =  28) or olanzapine (10 mg/kg/day, n =  28). In addition, brain sections from subgroups of sedentary animals ( n =  8) were co-immunolabeled with antibodies against vesicular GABA (VGAT) and glutamate (VGLUT1) transporters, along with syntaxin-1, and examined by confocal microscopy to detect selective olanzapine effects within inhibitory or excitatory terminals. Following olanzapine treatment, sedentary, but not exercising rats showed downregulated (33–50%) hippocampal densities of SNARE proteins and synaptotagmin, without altering complexin levels. Strikingly, these effects had no consequences on the amount of SNARE protein–protein interactions. Lower immunodensity of presynaptic proteins was associated with reduced CA1 volume and glucose intolerance. Syntaxin-1 depletion appeared more prominent in VGAT-positive terminals within the dentate gyrus, and in non-VGAT/VGLUT1-overlapping areas of CA3. The present findings suggest that chronic exposure to olanzapine may alter hippocampal connectivity, especially in inhibitory terminals within the dentate gyrus, and along the mossy fibers of CA3. Together with previous studies, we propose that exercise-based therapies might be beneficial for patients being treated with olanzapine.